A RETROSPECTIVE STUDY OF COMPARISION OF OUTCOMES BETWEEN PARA-UMBILICAL AND TRANS-UMBILICAL PORT INSERTION FOR LAPAROSCOPIC SURGERIES (Indian Journal of Applied-Basic Medical Sciences, 2020)
Objective: The study was undertaken to compare the intra operative feasibility, post operative pain, cosmetic results and complications between the para-umbilical and trans-umbilical techniques of laparoscopic port insertion.Methodology: This was a comparative study carried out at a tertiary care hospital from January 2018 to January 2019. 50 patients enrolled in the study for laparoscopic surgeries were equally divided into 2 groups, Group A (25) – Para-umbilical port insertion group and Group B (25) – Trans-umbilical port insertion group.Results: In both the groups’ operation time, post-operative analgesic requirement and patient satisfaction were similar. Two cases (8%) in the para-umbilical and three cases (12%) in the Trans-umbilical group developed wound infections. The umbilical port site complications rates were comparable (P > 0.05).Conclusion: The trans-umbilical incision is relatively easier to perform and has better cosmetic results and seems to be a safe and feasible alternative to the para-umbilical incision for Laparoscopic surgeries.
Keywords: Para-umbilical; Trans-umbilical; Laparoscopic technique; Patient Satisfaction